2008
DOI: 10.1007/s10637-008-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of the anti-glycolytic activity of 3-bromopyruvate confirmed by FDG uptake in a rat model of breast cancer

Abstract: Our study showed that 3-BrPA exhibits a strong anti-glycolytic effect on RMT cells implanted in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 22 publications
3
14
0
Order By: Relevance
“…3-Bromopyruvate (3-Br-PA) was reported to deplete cancer cells of ATP and to have antitumor effects against hepatocellular carcinoma in rats (43) without damage to normal tissues. Similar reports described activity against breast carcinoma in rats (44). 3-Br-PA is an alkylating agent that has a structural similarity to lactate (43).…”
Section: Starvation Of Cancer Cellssupporting
confidence: 74%
“…3-Bromopyruvate (3-Br-PA) was reported to deplete cancer cells of ATP and to have antitumor effects against hepatocellular carcinoma in rats (43) without damage to normal tissues. Similar reports described activity against breast carcinoma in rats (44). 3-Br-PA is an alkylating agent that has a structural similarity to lactate (43).…”
Section: Starvation Of Cancer Cellssupporting
confidence: 74%
“…The results from the current study establish that a low, non-cytotoxic dose of 3-BrPA is sufficient to induce metabolic perturbation in order to elevate the surface expression level of MICA/B. 3-BrPA has been shown to promote antitumor effects in many solid malignancies including liver, 30,31 breast, 32 pancreas, 33 brain 34 and colon cancers. 35 However, at the dose tested in this study, no cytotoxicity or antitumor effects "per se" have been reported.…”
Section: Discussionsupporting
confidence: 59%
“…The effects on HK, GAPDH, SDH and vacuolar H + ATPase mentioned above were observed in rat liver mitochondria and in normal rat thymocytes (Dell'Antone 2009); it was indeed proposed that above 20-30 μM, 3-BP may lead to severe toxic side effects (Dell'Antone 2006). Direct effects on highly ATPdependent spermatozoa have been reported (Jones et al 1996;Kumar et al 2008), and on similarly ATP-dependent kidney proximal tubule cells (Jones et al 1996); these findings are in line with effects on mitochondria and with increased uptake of FDG in liver and kidney (Vali et al 2008;Buijs et al 2009). Clearly, more investigation of 3-BP effects on normal cells is warranted.…”
Section: Tumor Specificity In Vivo Studies and Toxicitymentioning
confidence: 72%